1998
DOI: 10.1177/095968019841002
|View full text |Cite
|
Sign up to set email alerts
|

The Sexual Division of Labour in Process Manufacturing: Economic Restructuring, Training and `Women's Work'

Abstract: It is widely assumed that the development of enhanced skills appropriate to advanced technologies is an important means of increasing the employability of the socially excluded. This article tests this assumption through case studies in the food industry in Austria, Germany and Britain. The findings indicate that organizational restructuring, technological change and redeployment of labour have very different consequences for women and for men. In all three countries the restructuring of work and skills increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
2

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 6 publications
1
12
0
2
Order By: Relevance
“…Women, by contrast, are more likely to be found in occupations defined as low skilled where management continues to feel that competition on costs is the most viable option. This is confirmed by a recent crossnational comparison of the food industry, which found that the restructuring of work and skills increased the marginalization of women, reinforcing gender cleavage (Flecker et al 1998; see also Wood 1986). The lower-quality upskilling experienced by women and their lower degree of involvement than men in performance management systems may well be leading to a gender gap in the quality of performance (White 1999).…”
Section: Trade Unions As Masculine Organizationssupporting
confidence: 53%
“…Women, by contrast, are more likely to be found in occupations defined as low skilled where management continues to feel that competition on costs is the most viable option. This is confirmed by a recent crossnational comparison of the food industry, which found that the restructuring of work and skills increased the marginalization of women, reinforcing gender cleavage (Flecker et al 1998; see also Wood 1986). The lower-quality upskilling experienced by women and their lower degree of involvement than men in performance management systems may well be leading to a gender gap in the quality of performance (White 1999).…”
Section: Trade Unions As Masculine Organizationssupporting
confidence: 53%
“…In some studies, men are found to have better options in the labour market, and are therefore viewed as more employable (McQuaid & Lindsay, 2005). Moreover, it has also been argued that the development of the labour market has gone in a direction that favours men's possibilities of finding employment (Flecker, Meil, & Pollert, 1998 …”
Section: Demographicsmentioning
confidence: 99%
“…In the Anglo-Saxon literature in particular, a great deal of attention is paid to the employability of so-called 'underprivileged' groups. Examples of 'underprivileged' groups found in the literature on employability include unmarried mothers [14], young people [15,31], elderly people [42], disabled people [43][44][45], women [46] and ethnic minorities [47,48]. Much of this literature focuses on formulating policy recommendations to strengthen the labour market position of these groups.…”
Section: Abilitymentioning
confidence: 99%